Exploring Students’ Perceptions of AI-Integrated E-Book in Healthcare ESP Courses - -, Surip Haryani; Emha, Maulida Rahmawati (ELITE JOURNAL, 2025)
The fast growth of artificial intelligence (AI) has created new opportunities for technology-enhanced language learning, especially in English for Specific Purposes (ESP) for health science students. This study explores students’ perceptions of an AI-integrated interactive e-book developed for health science ESP courses. A mixed-method design was employed with 55 students from Nursing, Midwifery, and Pharmacy programs at Universitas Madani. Data were collected through a Likert-scale questionnaire and reflective responses. The descriptive analysis showed an overall mean perception score of 76.51 (SE = 1.814; 95% CI = 72.87–80.15), with a median of 81.00, higher than the mean, suggesting above-average perceptions for most students. A standard deviation of 13.455 indicated considerable variation, with scores ranging from 39 to 90 (range = 51; IQR = 18). Item-level means ranged from 4.0 to 4.4, indicating positive responses in terms of accessibility, navigability, relevance of AI features, and motivational impact. Qualitative reflections revealed that students valued adaptive learning, real-time feedback, and improved confidence in medical English communication, while challenges included internet connectivity, chatbot limits, and initial adjustment. Overall, the AI-integrated e-book was perceived as useful, engaging, and relevant, though further improvements such as multimedia and simulations. This study concludes that AI-powered e-books have strong potential to advance ESP instruction in healthcare education.